The Effect of Profitability, Capital Structure and Firm Size on Firm Value (Study on Pharmaceutical Companies Listed on The Indonesia Stock Exchange 2016-2020) - Rachmawati, Windasari; Handayani, Esmiaty; Karim, Abdul (Economics and Business Solutions Journal, 2022)
The purpose of this study is to examine the factors that affect firm value. Some of the factors used are profitability, capital structure, and firm size which aims to test profitability, capital structure and firm size empirically that affect the value of companies in the pharmaceutical sector listed on the Indonesia Stock Exchange (IDX) in 2016-2020. During 2016-2020, several pharmaceutical companies did not have company assets that were financed from equity or own capital. This is because the factors that affect the value of the company, namely profitability, capital structure, and company size do not have a high value so that the company's assets are financed by debt. However, some of these pharmaceutical companies own their assets financed by equity because these companies are well-known companies and already have stable quality and performance. The population of this study was 12 pharmaceutical companies listed on the Indonesia Stock Exchange in 2016-2020. Sampling is using purposive sampling technique, in order to obtain a sample of 10 companies with a total of 50 data in 2016-2020. The results of this study indicate that profitability has a significant effect on firm value, capital structure has a significant effect on firm value, and firm size has no significant effect on firm value.Keywords: Profitability, Capital Structure, Firm Size, Firm Value